RISK ANALYSIS OF CABBAGE FARMING IN SELUPU REJANG DISTRICT, REJANG LEBONG REGENCY - Damayanti, Destin; Yuliarti, Ellys; Sumantri, Bambang; Alfayanti (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2025)
The purpose of this study was to analyze the level of production risk, price risk, and cost risk in cabbage farming in Selupu Rejang District, Rejang Regency, Bengkulu Province. This research used descriptive quantitative method with survey approach. The research sample was 92 cabbage farmers selected by purposive sampling from the four largest cabbage producing villages. Data analysis was done by calculating the mean, variance, standard deviation, coefficient of variation, and lower limit. Based on the results of the study, it is known that the level of risk of production, price, and cost is low because the CV value <0.5 with a production CV value of 0.0013, a price CV value of 0.0018 and a cost CV value of 0.000033. In addition, the value of the lower limit (L) is more than 0, which means that farmers have the opportunity to experience profits with a production L value of 570,228, a price L value of 320,865, and a cost L value of 936,009,909.Keywords: risk, farming, cabbage.